Elements of moral cognition : Rawls' linguistic analogy and the cognitive science of moral and legal judgment - Mikhail, John M., 1969- (Cambridge studies in law and society., 2011)
John Mikhail explores whether moral psychology is usefully modelled on aspects of Universal Grammar.